Exploring the Relationship Between Procrastination and Academic Stress in University Students - Pangestu, DWI; Puspitasari, Indah; Woro Listyorini, Meria; Shoaliha, Maratun (Nursing Genius Journal, 2025)
Background: Academic procrastination is commonly observed among university students, often associated with academic stress, particularly in health sciences programs where academic demands are substantial.  Methods: A pre-experimental study was conducted at Siloam Hospitals Lippo Village involving 39 participants meeting specific inclusion criteria (PIVAS score 2–3, age ≥3 years, and consent to participate). Additionally, a cross-sectional survey was administered to 178 university students from Bani Saleh University to assess levels of procrastination and academic stress. Data were analyzed using univariate and bivariate statistical methods, including paired t-tests and Wilcoxon signed-rank tests for clinical measures, and correlation analysis for student responses. Results: The majority of student participants were late adolescents (98.3%), female (88.4%), and enrolled in undergraduate programs (55.2%). Procrastination levels were predominantly moderate (95.6%), as were academic stress levels (59.7%). Age was found to have a moderating effect on stress management capacity, with older students exhibiting better coping mechanisms. Although female students dominated nursing programs due to cultural and personal factors favoring caregiving roles, they also reported higher stress levels, potentially influenced by hormonal and psychosocial factors. Conclusion: No statistically significant association was found between procrastination and academic stress (P = 0.417). These findings suggest that while both variables are prevalent, they may operate independently, influenced by distinct underlying factors.